Chest Tomosynthesis: Technical and Clinical Perspectives - Johnsson, Ase Allansdotter; Vikgren, Jenny; Bath, Magnus (Seminars in Respiratory and Critical Care Medicine, 2014)
The recent implementation of chest tomosynthesis is built on the availability of large, dose-efficient, high-resolution flat panel detectors, which enable the acquisition of the necessary number of projection radiographs to allow reconstruction of section images of the chest within one breath hold. A chest tomosynthesis examination obtains the increased diagnostic information provided by volumetric imaging at a radiation dose comparable to that of conventional chest radiography. There is evidence that the sensitivity of chest tomosynthesis may be at least three times higher than for conventional chest radiography for detection of pulmonary nodules. The sensitivity increases with increasing nodule size and attenuation and decreases for nodules with subpleural location. Differentiation between pleural and subpleural lesions is a known pitfall due to the limited depth resolution in chest tomosynthesis. Studies on different types of pathology report increased detectability in favor of chest tomosynthesis in comparison to chest radiography. The technique provides improved diagnostic accuracy and confidence in the diagnosis of suspected pulmonary lesions on chest radiography and facilitates the exclusion of pulmonary lesions in a majority of patients, avoiding the need for computed tomography (CT). However, motion artifacts can be a cumbersome limitation and breathing during the tomosynthesis image acquisition may result in severe artifacts significantly affecting the detectability of pathology. In summary, chest tomosynthesis has been shown to be superior to chest conventional radiography for many tasks and to be able to replace CT in selected cases. In our experience chest tomosynthesis is an efficient problem solver in daily clinical work.
Keywords: chest; radiography; tomosynthesis; computed tomography